Implementasi Program Sekolah Plus Ngaji dalam Meningkatkan Kemampuan Membaca Al-Qur’an di SDN 9 Tambakasri - Ridwan Fausi; Yazidul Busthomi (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2025)
This study aims to evaluate the implementation of the Sekolah Plus Ngaji (School Plus Quran Recitation) Program at SDN 9 Tambakasri and its impact on improving students’ Quran reading abilities. The main issue behind this research is the low proficiency of elementary school students in reading the Quran, caused by limited religious education time, lack of parental support at home, and ineffective teaching methods. This research employed a qualitative descriptive approach with data collection techniques including observation, in-depth interviews, documentation, and Quran reading tests. The results indicate that the program is conducted regularly three times a week using habit-building strategies, group mentoring, and periodic evaluations. A significant improvement was observed in students' Quran reading skills after participating in the program, as shown by a decrease in the number of students at the basic reading level and an increase in those with fluent reading ability. Additionally, there was a positive shift in students' attitudes toward religious learning, including greater confidence and improved understanding of Quranic recitation rules. The success of the program was also supported by active parental involvement and strong collaboration between teachers, schools, and families. However, challenges such as limited instructional time and a lack of supportive learning resources remain. In conclusion, the Sekolah Plus Ngaji Program is effective in enhancing students’ Quran reading skills and religious character formation when supported by proper implementation strategies and stakeholder cooperation.